M. Šlapelienės knygynas Vilniuje. II. Leidybinė veikla, asortimentas, komerciniai ryšiai, informacijos priemonės - Vaičiūnaitė, Aušra (Knygotyra, 1995)
The bookshop of M. Šlapelienė had great importance for advancing of Lithuanian culture. It not only extented trade of Lithuanian and lithuanistic books, but also proceeded publishing work. Since 1906 till 1945 it published 42 books. The biggest part of it’s published production consisted of education literature. Dictionaries, compiled by J. Šlapelis, had an outstanding significance. The bookshop of M. Šlapelienė was acting without break for 39 years – very rare case in the history of Lithuanian bookshops. The most productive period of it’s work was in 1906–1914. It probably was due to increase of need of Lithuanian books after recovering of press. The bookshops in tsarist Russia were free of taxes, so they could have free commercial contacts with other countries. Therefore in 1914 the bookshops Wars, national oppression carried out by occupation authorities made the work of the bookshop very difficult, because it was constantly under control. The years of polish occupation were the worst ones, as additional difficulties about getting books from Lithuania appeared. The commercial contacts with other countries also declined. During the war (in 1914) the bookshop had an important mission – to suply with books and text-books new established lithuanian schools. Lithuanian libraries purchased in this bookshop all Lithuanian books. The bookshop of M. Šlapelienė has done big cultural-educational work.